Constraining CMIP6 simulations for Atlantic Water in the Arctic using an AMOC-SST index - Devilliers, Marion; Olsen, Steffen M.; Langehaug, Helene R.; Guo, Chuncheng; Mahmood, Rashed; Tian, Tian; Yang, Shuting (Frontiers in Climate, 2025)
Atlantic Water plays a key role in future changes in the Arctic Ocean. It contributes to Atlantification by transporting salt and heat within the Arctic Ocean basins. Many studies also attribute the amplified warming of the Arctic Ocean to an increase in poleward ocean heat transport by warming currents or the increasing strength of ocean currents. Global models are needed to reliably predict consistent trends in heat transport, as large-scale processes are at play. However, these models are too coarse to resolve key ocean processes and to address the complex interplay between ocean dynamics and the bathymetry of the Arctic region. Here, we propose to construct a sub-ensemble of simulations based on 235 historical simulations from 12 CMIP6 models that best represent the downstream drivers of Atlantic warming. We select the model ensemble members showing the closest agreement with observed surface temperature variability over 1960–1990 in the subpolar gyre (SPG). More specifically, we use a recent index that links surface temperature in the SPG to the Atlantic Meridional Overturning Circulation (AMOC): the AMOC-SST index. The subsampled ensemble shows a better correlation with the observed AMOC-SST index over the last 35 years of the historical period (1980–2014). It also displays a reduced error and better correlation for the Atlantic Water core temperature and depth in the Eurasian Arctic Ocean when compared to reanalysis and observations. Overall, the AMOC-SST index-based selection leads to a systematic improvement in the representation of the Atlantic Water layer in the Eurasian Arctic region, suggesting a clear connection between the Arctic Ocean and surface temperature in the subpolar region, and by extension, possibly the AMOC.